Enhancing Literacy And Reading Interest Among The Community Of Sandosi Village Through The Unwira Reading Centre - Kristianus Simon Hale Molan; Yosef Lamawuran; Frans Bapa Tokan (Bakti Cendana, 2026)
This community service activity aims to enhance reading interest and digital literacy skills among the residents of Sandosi Village through the optimisation of the Unwira Reading House. The programme was conducted over three months, from March to May 2025, involving fifty participants comprising children, teenagers, and parents. A participatory approach was adopted to ensure the community played an active role in every stage of the activity. Implementation methods included a situational analysis, the provision of additional reading materials, group reading sessions, basic digital literacy training, and evaluation using pre-test and post-test instruments. The results of the activities showed an average increase in literacy skills from 58% to 87%, with more positive changes in learning behaviour, particularly among children and teenagers. The Unwira Reading House, which had previously been underutilised, is now once again being used as a shared learning space. Although the activities still face limitations in terms of facilities and internet connectivity, these results demonstrate that simple, community-based literacy initiatives can have a tangible impact on improving literacy at the village level.